Mini-Review: Limbal Stem Cells Deficiency in Companion Animals: Time to Give Something Back?. (2nd April 2016) - Sanchez, Rick F.; Daniels, Julie T.
Abstract: Experimental animals have been used extensively in the goal of developing sight-saving therapies for humans. One example is the development of transplantation of cultured limbal epithelial stem cells (LESC) to restore vision following ocular surface injury or disease. With clinical trials of cultured LESC therapy underway in humans and a potential companion animal population suffering from similar diseases, it is perhaps time to give something back. Comparatively to humans, what is known about the healthy limbus and corneal surface physiology of companion animals is still very little. Blinding corneal diseases in animals such as symblepharon in cats with Feline Herpes Virus-1 infections require a basic understanding of the functional companion animal limbus and corneal stem cells. Our understanding of many other vision threatening conditions such as scarring of the cornea post-inflammation with lymphocytic–plasmacytic infiltrate in dogs (aka chronic superficial keratitis) or pigment proliferation with Pigmentary Keratitis of Pugs would benefit from a better understanding of the animal cornea in health and disease. This is also vital when new therapeutic approaches are considered. This review will explore the current challenges and future research directions that will be required to increase our understanding of corneal diseases in animals and consider the potential development and delivery of cultured stem cell therapy to veterinary ocular surface patients.